Acrolein-induced autophagy–dependent apoptosis via activation of the lysosomal–mitochondrial pathway in EAhy926 cells. (October 2018) - Luo, Songsong; Jiang, Liping; Li, Qiannan; Sun, Xiance; Liu, Ting; Pei, Fuyang; Zhang, Tianjiao; Liu, Tiehong; Dong, Linlin; Liu, Xiaofang; Jiang, Lijie
Abstract: Acrolein, a highly reactive α, β-unsaturated aldehyde, is a toxic component of cigarette smoke. As a lipid peroxidation biomarker, acrolein plays an important role in a wide variety of disease states, such as neurodegenerative, Alzheimer's disease, diabetes and atherosclerosis. Endothelial cell injury is one of the initiating factors of atherosclerosis, but the underlying molecular mechanisms remain unclear. Our study primarily focused on acrolein-induced autophagy–dependent apoptosis and the possible molecular mechanism. The results showed that treatment with acrolein increased the number of intracellular GFP-LC3 II punctuates and the expression of autophagosome biomarker LC3-II, with the low dose (25 μM) or at the early stage of treatment (3 h). Following treatment of EAhy926 cells with acrolein for 6 h, lysosomal permeabilization changed, and cathepsin B (CB) was released. Additionally, acrolein induced the collapse of mitochondrial transmembrane potential, and cytochrome c was released. Furthermore, caspase-3 and caspase-9 activation showed that acrolein induced EAhy926 cell apoptosis. Autophagy inhibitor 3MA and CB inhibitor CA-074 Me (CA) attenuated acrolein-induced apoptosis. Collectively, our results suggested that acrolein-induced apoptosis is autophagy-dependent, occurring via injury to lysosomes and mitochondria. This study provides new mechanistic insight toward understanding the pathogenesis of acrolein-related disorders. Highlights: Acrolein induced autophagy–dependent apoptosis in EAhy926 cells. Lysosomal–mitochondrial pathway is responsible for acrolein –induced apoptosis. Acrolein-induced apoptosis could involve the release of cathepsin B and cytochrome c .